Information Management: Weick's Organizational Information Theory Approach - Noorzihidayah Md Noor; Maizatul Haizan Mahbob; Mohd Azul Mohamad Salleh; Wan Amizah Wan Mahmud; Muhammad Adnan Pitchan Ahmad Harakan (Journal of Public Administration and Government, 2023)
This concept paper discusses the role of information management in organization through Organizational Information Theory approach by Karl E. Weick. Information management is important for an organization because it can drive organizational excellence . A growing environment complex needs management efficient information as well as an effective training and development program. This is very significant especially when there is a conflict or crisis. Thus, the objective of this paper is to discuss previous studies related to organizational information management and how information management contributes to several factors of organizational excellence. This paper used a systematic evaluation analysis to search past studies related to this matter. In the context of information management, the themes covered are the information environment, the ambiguity of information and the interpretation of information which is seen as an important strategy to deliver messages to every level involved in an organization.